SCIENTIFIC COGNITION IN THE ERA OF INFORMATION TECHNOLOGIES - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
Th article investigates the features of the process of scientific knowledge in the era of information technologies.